The Policing of Private Conscience: Literary Interjections on Public Morals - Wakefield, Mark J. R. (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2021)
The human experience is a complex and unique thing. Humankinds‟ attempt to give shape to its own perception of existence goes to the heart of the aesthetic experience but faces obstacles to its realisation. This text seeks to explore the cultural currents that interact with literary works that act as a counterweight to censorial forces which manifest themselves in many forms throughout the ages.